Bodies in conflict
1 online resource (xix, 228 pages)
Keywords: "Twentieth-century war is a unique cultural phenomenon and the last two decades have seen significant advances in our ability to conceptualize and understand the past and the character of modern technological warfare. At the forefront of these developments has been the re-appraisal of the human body in conflict, from the ethics of digging up First World War bodies for television programmes to the contentious political issues surrounding the reburial of Spanish Civil War victims, the relationships between the war body and material culture (e.g. clothing, and prostheses), ethnicity and identity in body treatment, and the role of the 'body as bomb' in Iraq, Afghanistan and beyond. Focused on material culture, Bodies in Conflict revitalizes investigations into the physical and symbolic worlds of modern conflict and that have defined us as subjects through memory, imagination, culture and technology. The chapters in this book present an interdisciplinary approach which draws upon, but does not privilege archaeology, anthropology, military and cultural history, art history, cultural geography, and museum and heritage studies. The complexity of modern conflict demands a coherent, integrated, and sensitized hybrid approach which calls on different disciplines where they overlap in a shared common terrain - that of the materiality of conflict and its aftermath in relation to the human body. Bodies in Conflict brings together the diverse interests and expertise of a host of disciplines to create a new intellectual engagement with our corporeal nature in times of conflict"--